Актуальні питання участі захисника в окремій процесуальній дії в кримінальному провадженні - Абламський, С. Є.; Ablamskyi, S. Ye.; Абламський Сергій Євгенович (Вісник Харківського національного університету внутрішніх справ. - 2017. - № 3 (78). - С. 38–45, 2017)
Досліджено процесуальний порядок залучення захисника для участі в окремій процесуальній дії, що можливо у трьох законодавчо передбачених невідкладних випадках. Звернено увагу на відсутність законодавчо закріплених визначень таких термінів, як «невідкладні випадки» та «невідкладні процесуальні дії», що може призвести до порушення права на захист і визнання судом недопустимими отриманих доказів. З урахуванням проведеного аналізу запропоновано до КПК України внести певні зміни й доповнення.

The author has studied the procedure for bringing in a defense attorney to participate in a certain procedural action, which is possible within three statutory urgency cases. In particular, the defense attorney is involved exclusively in urgent cases, when: 1) there is a need for conducting an urgent procedural action with the participation of the defense attorney, and the notified advocate can not arrive to participate in the procedural action or to ensure the participation of another attorney; 2) a suspect, an accused expressed a wish, but had not managed to attract a lawyer yet; 3) the arrival of the chosen defense attorney is impossible. It has been noted that, on the one hand, such requirements are additional guarantees of protecting the rights of a suspect, an accused, and on the other, they eliminate the possibility of delaying the process of considering the proceedings on the merits by lawyers and defendants, since in some cases the defendant objects to bringing a defense attorney to conduct a certain procedural action, referring to the fact that his lawyer did not refuse to provide legal aid. Special attention has been paid to the absence of a legislative definition of such terms as “urgent cases” and “urgent procedural actions”, which, in the author’s opinion, may lead to the violation of the right to protection and the court’s recognition of inadmissible of the obtained evidence. That is, those actions, when the delay of their conduction may lead to the loss of evidence, the disappearance, damage of objects that may subsequently become material evidence, or the traces of the crime or persons who has committed it, as well as the actions that facilitate to establish the concrete concise deadlines according to the Criminal Procedural Code of Ukraine. Taking into account the carried out analysis, the author has suggested to make certain amendments and alterations in the Criminal Procedural Code of Ukraine aimed at eliminating existing legislative gaps and inaccuracies.

Исследован процессуальный порядок привлечения защитника для участия в отдельном процессуальном действии, что возможно в трёх законодательно предусмотренных неотложных случаях. Обращено внимание на отсутствие законодательно закрепленных определений таких терминов, как «неотложные случаи» и «неотложные процессуальные действия», что может привести к нарушению права на защиту и признанию судом недопустимыми полученных доказательств. С учётом проведенного анализа предложено в УПК Украины внести определенные изменения и дополнения, направленные на устранения существующих законодательных пробелов и неточностей.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; захисник; право на захист; правнича допомога; правова допомога у кримінальних справах; процесуальні дії; невідкладні випадки; підозрюваний; обвинувачений; defender; right to protection; legal aid; procedural actions; urgent cases; suspect; accused; защитник; право на защиту; юридическая помощь; правовая помощь по уголовным делам; процессуальные действия; неотложные случаи; подозреваемый; обвиняемый